2020
DOI: 10.3389/fneur.2020.00337
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic Solutions for Stroke Recovery and Improved Quality of Life in Low- and Middle-Income Countries—A Systematic Review

Abstract: Background: Given the limited healthcare resources in low and middle income countries (LMICs), effective rehabilitation strategies that can be realistically adopted in such settings are required. Objective: A systematic review of literature was conducted to identify pragmatic solutions and outcomes capable of enhancing stroke recovery and quality of life of stroke survivors for low- and middle- income countries. Methods: PubMed, HINARI, and Directory o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 390 publications
(299 reference statements)
1
7
0
Order By: Relevance
“…Knowledge of stroke risk factors is expected to substantially contribute to secondary stroke prevention by improving stroke literacy among stroke survivors, especially in Nigeria and other LMICs where stroke survivors have been reported to lack knowledge of stroke, its risk factors and warning signs. 6,31,32 The contents of this educational tool are in line with the themes featured in the study of Maniva et al, 14 . The tool was validated by stroke rehabilitation experts, consistent with previous studies in which a new tool was developed and the items were assessed for content validation.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Knowledge of stroke risk factors is expected to substantially contribute to secondary stroke prevention by improving stroke literacy among stroke survivors, especially in Nigeria and other LMICs where stroke survivors have been reported to lack knowledge of stroke, its risk factors and warning signs. 6,31,32 The contents of this educational tool are in line with the themes featured in the study of Maniva et al, 14 . The tool was validated by stroke rehabilitation experts, consistent with previous studies in which a new tool was developed and the items were assessed for content validation.…”
Section: Discussionsupporting
confidence: 56%
“…Knowledge of stroke risk factors is expected to substantially contribute to secondary stroke prevention by improving stroke literacy among stroke survivors, especially in Nigeria and other LMICs where stroke survivors have been reported to lack knowledge of stroke, its risk factors and warning signs. 6, 31, 32…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After training, the functional status of the ischemic stroke survivors and decreased their complications. 13,14 did a systematic review and found that the pragmatic solution to stroke recovery and improved quality of life in low-and middle -income countries is to have low -cost rehabilitation techniques demonstrated to the caregivers of the patients. Given the importance of improving caregivers' knowledge and the greater need to improve the quality of life of caregivers and patients, this study was conducted to test an educational intervention.…”
Section: Introductionmentioning
confidence: 99%
“…In low-and middle-income countries (LMICs), the incidence of stroke is rising, and research shows that stroke-related mortality tripled between 2002 and 2020 in Latin America, the Middle East, and sub-Saharan Africa [6,7]. While the same mortality is increasing in low-income countries compared to highincome countries, and there is a much greater reduction in stroke mortality in high-income countries as compared to low-income countries [8].…”
mentioning
confidence: 99%